2017
DOI: 10.1016/j.expthermflusci.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Condensation heat transfer and pressure drop characteristics of R-600a in horizontal smooth and helically dimpled tubes

Abstract: In the present study, condensation heat transfer and frictional pressure drops of refrigerant R-600a (iso-butane) inside a helically dimpled tube and a plain tube of internal diameter 8.3 mm were measured and analyzed. All tests were performed at different vapor qualities up to 0.82 and average saturation temperatures ranging between 38 and 42℃. Refrigerant mass fluxes varied in the range of 114-368 kg/m 2 s. The inner surface of the helically dimpled tube has been designed and reshaped through three-dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…A similar study with dimples and protrusions in microchannels using Al 2 O 3 ‐Water nanofluids was conducted by Li and colleagues, Dimpled vortex generators in lattice cooling channels showed superior heat transfer capabilities due to increases in surface area . Several other similar studies on enhanced tubes with dimples in channels and tubes were performed by various researchers as reported in the literature …”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…A similar study with dimples and protrusions in microchannels using Al 2 O 3 ‐Water nanofluids was conducted by Li and colleagues, Dimpled vortex generators in lattice cooling channels showed superior heat transfer capabilities due to increases in surface area . Several other similar studies on enhanced tubes with dimples in channels and tubes were performed by various researchers as reported in the literature …”
Section: Introductionmentioning
confidence: 59%
“…20 Several other similar studies on enhanced tubes with dimples in channels and tubes were performed by various researchers as reported in the literature. [21][22][23][24][25][26] At this stage, it is important to study heat transfer behavior with different spacings between the tubes, because no such study has yet been performed. Hence, with this motivation, an experimental study is reported in this article to address the heat transfer enhancement at different spacings of the tubes.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the dimpled tube with the largest depth provided the highest heat transfer coefficient, as well as the largest pressure drop penalty (an unexpected pressure drop increase up to 892% higher than that of the smooth tube was reported). Sarmadian et al [14] measured and analyzed the condensation heat transfer coefficient and frictional pressure drop of R600a in a helically dimpled tube. Their experimental results indicated that the heat transfer coefficients of the dimpled tube were 1.2-2 times higher than those found in an equivalent smooth tube with a pressure drop penalty ranging from 58% to 195% (when compared to smooth tubes).…”
Section: Introductionmentioning
confidence: 99%
“…In another empirical study performed by Shafaee et al [17] on boiling of R-600a in plain and rough pipes, it was demonstrated that heat transfer rate and pressure drops in dimpled pipes are larger than those obtained in smooth pipes. To illustrate the impacts of operational conditions and pipe surface roughness on the magnitude of heat transfer coefficient and pressure loss obtained during condensation of R-600a, Sarmadian et al [18] evaluated a two-phase flow heat-exchanger. According to the observations, increasing the vapor quality and mass flux gives rise to the rate of transferred heat and pressure loss.…”
Section: Introductionmentioning
confidence: 99%